The state-of-the-art of wire arc directed energy deposition (WA-DED) as an additive manufacturing process for large metallic component manufacture. Issue 3 (4th March 2023) - Costello, Sam C.A.; Cunningham, Chloe R.; Xu, Fangda; Shokrani, Alborz; Dhokia, Vimal; Newman, Stephen T.
ABSTRACT: Wire Arc Directed Energy Deposition (WA-DED) also known as Wire Arc Additive Manufacture (WAAM) is a niche additive manufacturing technique for metals that is increasingly offering a competitive advantage to traditional forging and casting methods. Characteristics of WA-DED are high deposition rates and feedstock that is inexpensive compared to powder processes, making it highly efficient for manufacture of large components. This paper reviews WA-DED as a technique for large component manufacture by assessing aspects of the process scalability. Arc processes are compared in terms of their production characteristics showing the relative suitability of each power source. Additional in-situ processes have been identified that can alleviate defects and improve mechanical performance. Investigation of process planning for WA-DED has revealed the potential for material savings that can be achieved by preventing accumulation of errors throughout manufacture. The major finding is that additional in-situ processes and process planning combined with a closed loop feed forward control system can significantly improve the process in terms of mechanical performance, geometric repeatability and resolution. Additionally, it was found that although the degree of isotropy of mechanical performance is commonly investigated, research into the heterogeneity of mechanical performance is limited, and does not assess tensile properties at different locations within deposited material.